Ceramic Coatings Resistant to Wear and Thermal Shock at High Temperatures (2023)
Beehive ovens made of red clay or adobe bricks are used in the coal coking industry. In the process, the furnaces are subjected to sudden changes in temperature that range from 1000 ◦C to 300 ◦C on average, in the removal process a steel rake is used to remove the coke, which causes abrasive wear due to friction between the rake, the coke, and the floor, at elevated temperatures. Over time, flooring deteriorates and needs to be replaced, leading to high maintenance costs. To prolong the service life of the furnace floor, it is lined with a material resistant to wear at high temperatures. One of the best performing materials under these conditions is zirconia, which when properly mixed with alumina provides excellent surface protection against wear and thermal shock. For the preparation of the coatings, the thermal projection technique with oxyacetylene flame was chosen, due to its versatility and economy. The coatings are characterized morphologically with MO optical microscopy and scanning electron microscopy SEM, the microstructure is analyzed by XRD diffraction, the wear resistance with tribometer in ball-disc configuration at room temperature and 500 ◦C without abrasive, microhardness with Vickers notches and resistance to thermal shock with cycles of heating to 500 ◦C, and cooling to room temperature. It is found that all coatings exhibited much higher wear resistance than the uncoated substrate by at least one order of magnitude and that the coating protected the substrate through at least 30 thermal shock cycles.